Inclusive methodologies from the teaching perspective for improving performance in university students with disabilities - Alejandro Lorenzo-Lledó; Gonzalo Lorenzo; Asunción Lledó; Elena Pérez-Vázquez (OmniaScience, 2020)
One of the challenges proposed by the European framework for higher education has been to develop a quality and accessible university education in order to reduce situations of exclusion of disabled students. In this sense, it is essential to reduce the existing gap in the academic performance of this group with respect to other students. The general objective of this study has been to analyze the application of inclusive methodologies in university students with disabilities from a teaching perspective. The adopted methodology was non-experimental quantitative with a sample of 313 teachers from the University of Alicante who have taught students with disabilities and who responded to a questionnaire designed ad hoc of 51 items. The results obtained show that teachers frequently use visual aids and use the same materials both in theory and in practice. Concerning perceptions, teachers consider that students with disabilities should acquire the same skills as the rest of their classmates and it was not difficult for them to teach them. Furthermore, the results showed significant differences in perceptions according to the professional category and the branch of knowledge of the teachers. From the aforementioned, it can be concluded that, although positive changes are perceived in teaching methodologies, it is necessary to continue making progress in improving teaching practice and the quality of education that facilitates the conditions for the academic performance of people with disabilities in Spanish universities.